2020
DOI: 10.1111/dom.14252
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐individual variability in atrasentan exposure partly explains variability in kidney protection and fluid retention responses: A post hoc analysis of the SONAR trial

Abstract: Aim To evaluate whether atrasentan plasma exposure explains between‐patient variability in urinary albumin‐to‐creatinine ratio (UACR) response, a surrogate for kidney protection, and B‐type natriuretic peptide (BNP) response, a surrogate for fluid expansion. Methods Type 2 diabetic patients with chronic kidney disease (n = 4775) received 0.75 mg atrasentan for 6 weeks in the active run‐in period. Individual area under the concentration‐time‐curve (AUC) was estimated using a population pharmacokinetic model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…This plasma exposure can then be used to determine the individual benefit / risk balance but should ideally also take into account other relevant patient characteristics that determine the long-term risk on kidney and heart failure outcomes as well as likelihood to respond to atrasentan. 10 Dose selection, based on short-term changes in risk markers for kidney protection and fluid retention, translated in a favorable balance toward long-term kidney protection. In addition to plasma exposure, we found that other patient characteristics also influenced long-term treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This plasma exposure can then be used to determine the individual benefit / risk balance but should ideally also take into account other relevant patient characteristics that determine the long-term risk on kidney and heart failure outcomes as well as likelihood to respond to atrasentan. 10 Dose selection, based on short-term changes in risk markers for kidney protection and fluid retention, translated in a favorable balance toward long-term kidney protection. In addition to plasma exposure, we found that other patient characteristics also influenced long-term treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On an individual level, an estimate of plasma exposure can be obtained using the population pharmacokinetic model using dosing information, sampling information, and plasma‐concentration. This plasma exposure can then be used to determine the individual benefit / risk balance but should ideally also take into account other relevant patient characteristics that determine the long‐term risk on kidney and heart failure outcomes as well as likelihood to respond to atrasentan 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These trials performed with various ETA antagonists show reno-protective effects by reducing proteinuria in patients with chronic kidney disease and type 2 diabetes [12,21,22,34,36,42,54,61] which shows us that the results from a selective, cell-specific deletion of the ET receptors in the animal model are hardly transferable to human kidney diseases.…”
Section: Discussionmentioning
confidence: 99%